2019
DOI: 10.3390/ijms20174089
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Interactions between Whey Protein and Inulin and Changes in Physicochemical and Antioxidative Properties of the Complexes

Abstract: Whey protein and inulin at various weight ratios were dry heated at 60 °C for 5 days under relative humidity of 63%. The heated mixtures were found to have significant changes in browning intensity and zeta-potential compared to untreated mixture. Heated samples showed significantly lower surface hydrophobicity than untreated mixtures. Compared with untreated samples, dry-heated samples showed significantly higher 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) scavenging ability with whey protein to inulin mass ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Even though Di Cairano and co-workers found higher L*, a*, and b* values for cookies enriched with soluble inulin, they concluded that there is no definite trend in the literature regarding the impact of inulin on the color of baked products [ 49 ]. The limited effect of inulin on the color is also explained by the restricted rate of the Maillard reaction in which sugars originating from inulin could serve as raw materials; on the other hand, protein–inulin interactions can also influence color [ 50 ]. Furthermore, the a* and b* values decrease upon replacement of sugar by xylitol and increase by WP addition.…”
Section: Resultsmentioning
confidence: 99%
“…Even though Di Cairano and co-workers found higher L*, a*, and b* values for cookies enriched with soluble inulin, they concluded that there is no definite trend in the literature regarding the impact of inulin on the color of baked products [ 49 ]. The limited effect of inulin on the color is also explained by the restricted rate of the Maillard reaction in which sugars originating from inulin could serve as raw materials; on the other hand, protein–inulin interactions can also influence color [ 50 ]. Furthermore, the a* and b* values decrease upon replacement of sugar by xylitol and increase by WP addition.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 c also shows the ζ-potential of ZNP-FSG complexes subjected to various ultrasound and homogenization processes. The stability of complexes could be studied by measuring the electrostatic stability of the colloidal particles [ 49 ]. Particles with ζ-potentials more positive than +30 mV or more negative than −30 mV are normally considered stable [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…20,21 However, there have been only a few studies on WPI-inulin conjugates. 3,22 In this research, inulin was covalently linked to WPI through the Maillard reaction, which was proceeded by wet heating treatment with different reaction time. At the same time, the ultrasound-assisted wet heating method was used to prepare conjugates and the optimal preparation conditions were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…As a prebiotic, inulin plays an important role in regulating intestinal microbiota and represents excellent health benefits 20,21 . However, there have been only a few studies on WPI–inulin conjugates 3,22 . In this research, inulin was covalently linked to WPI through the Maillard reaction, which was proceeded by wet heating treatment with different reaction time.…”
Section: Introductionmentioning
confidence: 99%